What do we know about the life-history traits of widely hunted tropical mammals? - Vliet, N. van; Nasi, R. (Cambridge University Press, 2019)
We synthesize information on parameters useful for managing the hunting of two common mammal species that are important for local people in the Neotropics and Africa: Cuniculus paca and Philantomba monticola, respectively. We highlight the scarcity of data available on the parameters needed to manage these two species sustainably. As most of the studies were conducted > 40 years ago, we stress the need to supplement the information available using methodological and technical innovations. In particular, we call for new assessments covering the possible variations in parameter values across the species’ distribution ranges, and covering various anthropogenic contexts, to test density-dependent and compensatory processes that may explain the resilience of these species to hunting.